Acute exposure to fine particulate matter and cardiovascular hospital emergency room visits in Beijing, China. (January 2017) - Xu, Qin; Wang, Shuo; Guo, Yuming; Wang, Chao; Huang, Fangfang; Li, Xia; Gao, Qi; Wu, Lijuan; Tao, Lixin; Guo, Jin; Wang, Wei; Guo, Xiuhua
Abstract: Fine particulate matter (PM2.5 ) air pollution outbreaks have recently occurred frequently in China. However, evidence of the associations between short-term exposure to PM2.5 and cardiovascular morbidity is still limited in China. This study aimed to evaluate the associations between PM2.5 and hospital emergency room visits (ERVs) for cardiovascular diseases in urban areas in Beijing. Daily counts of cardiovascular ERVs were collected from ten large general hospitals from Jan 1 to Dec 31, 2013. Air pollution data were obtained from the Beijing Environmental Protection Bureau including 17 monitoring stations. A generalized additive Poisson model was used to examine the associations between PM2.5 and cardiovascular ERVs after controlling for seasonality, day of the week, public holidays, influenza outbreaks, and weather conditions. In total, there were 56, 221 cardiovascular ERVs during the study period. The daily mean PM2.5 concentration was 102.1 μg/m 3, ranging from 6.7 μg/m 3 to 508.5 μg/m 3 . Per 10 μg/m 3 increase in PM2.5 was associated with a 0.14% (95% confidence interval [ CI ]: 0.01%–0.27%) increase in cardiovascular ERVs at lag3 . Cumulative delayed estimates were greatest at lag0–5 (0.30%, 95% CI : 0.09%–0.52%). The estimates of percentage change in daily ERVs per 10 μg/m 3 increase in PM2.5 were 0.56% ( 95%CI : 0.16%–0.95%) for ischemic heart disease (IHD) at lag0–1, 0.81% ( 95%CI : 0.05%–1.57%) for heart rhythm disturbances (HRD) at lag0–1 and 1.21% ( 95%CI : 0.27%–2.15%) for heart failure (HF) at lag0, respectively. The effects of PM2.5 on IHD ERVs during high temperature days (>11.01 °C) were significantly higher than that on low temperature days (≤11.01 °C) at lag0, lag0–1, lag0–3 and lag0–5 ( P < 0.05). The study suggests that PM2.5 has acute impacts on cardiovascular ERVs in Beijing, especially on IHD, HRD and HF. The effects of PM2.5 on IHD ERVs vary by temperature. Highlights: We observed adverse short-term effects of PM2.5 on cardiovascular emergency room visits (ERVs). PM2.5 was significantly associated with ERVs for ischemic heart disease, heart rhythm disturbances and heart failure. We did not find significant cerebrovascular effects of PM2.5 The effects of PM2.5 on ischemic heart disease ERVs vary by temperature. Abstract : Our findings strengthen the evidence of the adverse short-term effects of PM2.5 on cardiovascular diseases morbidity in China.